2020
DOI: 10.3389/fnhum.2020.00081
|View full text |Cite
|
Sign up to set email alerts
|

Man’s Pursuit of Meaning: Unexpected Termination Bolsters One’s Autonomous Motivation in an Irrelevant Ensuing Activity

Abstract: Meaningfulness has been suggested as one of the fundamental psychological needs, as one would actively pursue meaning in both his/her work life and personal life. Previous studies consistently showed that a lack of meaning in work would reduce one's autonomous motivation in the current job, which is the motivation to engage in self-determined activities driven by one's own interests or personal beliefs. However, researchers overlooked the fact that in work settings, it is not uncommon that people work on multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…While it was unlikely to directly restore their perceived meaningfulness in the first experiment, they could still do meaningful work in the second experiment, which was why they increased their labor supply in image emotion‐labeling. Thus, our findings provided direct support for the fluid compensation hypothesis proposed by MMM and findings of a recent electrophysiological study which adopted a similar design (Wei, Mo, Liu, & Meng, 2020). As the pursuit and restoration of meaning of work in an irrelevant task is only one of the possible restorative responses, this study suggests new directions for subsequent studies on meaning restoration.…”
supporting
confidence: 88%
“…While it was unlikely to directly restore their perceived meaningfulness in the first experiment, they could still do meaningful work in the second experiment, which was why they increased their labor supply in image emotion‐labeling. Thus, our findings provided direct support for the fluid compensation hypothesis proposed by MMM and findings of a recent electrophysiological study which adopted a similar design (Wei, Mo, Liu, & Meng, 2020). As the pursuit and restoration of meaning of work in an irrelevant task is only one of the possible restorative responses, this study suggests new directions for subsequent studies on meaning restoration.…”
supporting
confidence: 88%
“…Thus, data in Session 2 were not analyzed. Based on grand averaged waveforms of the FRN and its anterior distribution reported in previous literatures (Zhou et al, 2010;San Martín, 2012;Meng and Ma, 2015;Fang et al, 2018;Wei et al, 2020) as well as observed in this study, amplitudes from the experimental group is a between-subject factor. In addition, a 3 (experimental group) × 2 (experimental session) mixed-design ANOVA was conducted to compare the number of successes (i.e., behavioral results).…”
Section: Resultssupporting
confidence: 52%
“…Thus, the RewP difference wave (the mean amplitude in response to wins minus that to failures) represents a rapid subjective evaluation of the motivational significance (Gehring and Willoughby, 2002;Yeung et al, 2005). Support for this can be found in previous studies reporting that a more pronounced RewP difference wave corresponds with greater perceived motivational significance (Masaki et al, 2006;Ma et al, 2011;Meng and Ma, 2015;Wei et al, 2020). For example, when the participants were instructed to perform a series of calculation tasks that require different amount of cognitive effort, a larger RewP difference wave would be observed when the participants were evaluating the outcome feedback for multiplications compared with additions.…”
Section: Introductionmentioning
confidence: 67%
“…While previous studies mainly examined effects of contextual factors and characteristics of the task itself on one's autonomous motivation (Deci and Ryan, 1985b;Bergin, 1999;Deci and Ryan, 2000;Gagné, 2014), our findings suggested that actually there are interplays between prior experience and one's motivation in the current activity. As it is a commonplace that a person would take part in several activities in a row, researchers may pay more attention to these dynamics and examine other influencing factors of one's motivation from an intertemporal perspective (Meng and Ouyang, 2020;Newton et al, 2020;Wei et al, 2020).…”
Section: Discussionmentioning
confidence: 99%